2009 10th International Conference on Document Analysis and Recognition 2009
DOI: 10.1109/icdar.2009.18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Retraining Rules for Semi-Supervised Learning in Neural Network Based Cursive Word Recognition

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Finally, the result shown that also when the cardinality of the new selected training set is negligible if compared to that of the initial training set, the feedback strategy is able to produce improvements. Future work will inspect deeply the possibility of evaluate the approaches on the task of semi-supervised learning as well as in unsupervised learning [24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the result shown that also when the cardinality of the new selected training set is negligible if compared to that of the initial training set, the feedback strategy is able to produce improvements. Future work will inspect deeply the possibility of evaluate the approaches on the task of semi-supervised learning as well as in unsupervised learning [24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…There are many applications in which user effort is limited or expensive. For instance, some applications need to build competent systems from scarce annotated data [9,11,21] in order to be used as soon as possible. Alternatively, in other applications complete annotation of documents is not required to convey the meaning, or to be used as source for other application, such as information retrieval [12].…”
Section: Computer Assisted Transcription Of Text Imagesmentioning
confidence: 99%
“…However, as there are unsupervised words, the system needs to select which words may be correct. So, we resort again to confidence measures to successfully adapt from high confidence unsupervised words by means of semisupervised learning [9].…”
Section: Semi-supervised Learningmentioning
confidence: 99%
“…This system is highly specialized after the adaptation and not suitable for general handwriting recognition, though. The task of unconstrained writer independent single word recognition was addressed in [6,7]. In this paper, we extend this approach by not restricting the focus on single, manually segmented words, but considering entire text lines.…”
Section: Introductionmentioning
confidence: 99%